Peran Mikrobioma Tanah dalam Peningkatan Produktivitas dan Ketahanan Tanaman - Ida Astina Laia; Natalia Kristiani Lase (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Global food demand continues to increase, but over-farming without considering environmental sustainability has led to land degradation. This can result in decreased crop yields. However, this problem can be solved by applying environmentally friendly farming methods using beneficial microbiomes that can improve soil health and increase crop productivity. This research aims to explore the role of the soil microbiome in enhancing crop productivity and crop resilience to biotic and abiotic stresses and supporting soil health, which enables the use of eco-agricultural approaches to solve these problems. This research utilizes the literature review technique, which involves analyzing, summarizing, evaluating and synthesizing documents from various references. This method aims to improve our understanding of how microorganisms promote plant growth in degraded soils. The results show that soil microbes improve soil quality and control plant diseases. Crop production on marginal lands can be sustainably increased with the use of the microbiome. In addition, the microbiome helps sustainable agriculture by reducing our dependence on synthetic chemicals, reducing environmental pollution and supporting food security worldwide, and supporting food security worldwide.